Enhancing Listening Skills through Project-Based Learning (PjBL) in Chokai 5 Class for JLPT N2 Preparation: A Classroom Action Research - Dirgandini, Melinda (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model in the Chokai 5 (listening) class. It is designed for those who wish to pass the JLPT N2. This research involved sixth-semester students of the Japanese Literature Study Program in Language and Culture Faculty of Maranatha Christian University. Using classroom action research (CAR), this study gathered the data using observations in pre-cycle, cycle 1, and cycle 2. In addition, this study also collected data through the simulation exam of JLPT N2 and the questionnaires on the students' perceptions of the PjBL model. The results of the study confirmed a substantial increase of 26.7% in the number of students achieving a minimum score after participating in the JLPT N2 listening simulation, compared to a pre-cycle frequency. The difference was statistically significant ( P <.05). The questionnaire results showed positive perceptions of learning using PjBL. Thus, it can be understood that the PjBL method can make students enthusiastic about independent learning to improve JLPT N2 listening score results.